Fast, feast, repeat : the comprehensive guide to delay, don't deny® intermittent fasting--including the 28-day fast start - Stephens, Gin (St. Martin's Griffin, 2020)
"Change when you eat and change your body, your health, and your life! Diets don't work. You know you know that, and yet you continue to try them, because what else can you do? You can Fast. Feast. Repeat. After losing over eighty pounds and keeping every one of them off, Gin Stephens started a vibrant, successful online community with hundreds of thousands of members from around the world who have learned the magic of a Delay, Don't Deny® intermittent fasting lifestyle. Fast. Feast. Repeat. has it all! You'll learn how to work a variety of intermittent fasting approaches into your life, no matter what your circumstances or schedule. Once you've ignited your fat-burning superpower, you'll get rid of "diet brain" forever, tweak your protocol until it's second nature, and learn why IF is a lifestyle, not a diet. Fast. Feast. Repeat. is for everyone! Beginners will utilize the 28-Day FAST Start. Experienced intermittent fasters will strengthen their intermittent fasting practice, work on their mindset, and read about the latest research out of top universities supporting intermittent fasting as the health plan with a side effect of weight loss. Still have questions? Gin has you covered! All of the most frequently asked intermittent fasting questions are answered in the exhaustive FAQ section"--